2020
DOI: 10.3390/bios10080091
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic-Based Electrochemical Immunosensing of Ferritin

Abstract: Ferritin is a clinically important biomarker which reflects the state of iron in the body and is directly involved with anemia. Current methods available for ferritin estimation are generally not portable or they do not provide a fast response. To combat these issues, an attempt was made for lab-on-a-chip-based electrochemical detection of ferritin, developed with an integrated electrochemically active screen-printed electrode (SPE), combining nanotechnology, microfluidics, and electrochemistry. The SPE surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 41 publications
(49 reference statements)
0
20
0
Order By: Relevance
“…The sensor was able to cover the clinical range of ferritin and showed an LOD of 0.413 ng mL −1 and was also to demonstrate the sensing capabilities in spiked serum samples. 134 On the basis of the literature survey on electrochemical based detection on oxidative stress markers, it is concluded that…”
Section: D Layered Materials Based (Bio)sensors For Oxidative Stress ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The sensor was able to cover the clinical range of ferritin and showed an LOD of 0.413 ng mL −1 and was also to demonstrate the sensing capabilities in spiked serum samples. 134 On the basis of the literature survey on electrochemical based detection on oxidative stress markers, it is concluded that…”
Section: D Layered Materials Based (Bio)sensors For Oxidative Stress ...mentioning
confidence: 99%
“…Electrochemical method for the detection of various oxidative stress markers (Reproduced with permission from ref . Copyright 2017 Elsevier; Reproduced from ref . Reproduced with permission from ref .…”
Section: D Layered Materials Based (Bio)sensors For Oxidative Stress ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Garg et al [ 83 ] developed a biosensor utilizing an active screen-printed electrode for continuous flow-based detection of serum ferritin. The sensing system comprised lab-on-chip technology integrated with an amine-functionalized graphene oxide SPCE, which allowed the continuous detection of ferritin in the range of 7.81–500 ng/mL.…”
Section: Infection-mediated Clinical Biomarkers and Their Electrical Biosensorsmentioning
confidence: 99%
“…Thus, an FET with a graphene-based biosensing medium is preferable for implementation in the rapid detection of infection-mediated clinical biomarkers.
Figure 5 ( A ) Electrochemical biosensors: ( a ) tungsten disulfide quantum dots-based electrochemical detection of serum ferritin (reprinted with permission from [ 80 ]), ( b ) handmade paper-based electrochemical sensing of serum ferritin (reprinted with permission from [ 85 ]), ( c ) microfluidic-based flow cell for serum ferritin detection (reprinted from [ 83 ]), and ( d ) nanorod-based electrical sensing of serum ferritin (reprinted with permission from [ 84 ]). ( B ) Electronic biosensors: ( a ) graphene-based FET (reprinted from [ 87 ]) and ( b ) nanowire-based FET (reprinted with permission from [ 86 ]).
…”
Section: Infection-mediated Clinical Biomarkers and Their Electrical Biosensorsmentioning
confidence: 99%